2005
DOI: 10.1103/physrevlett.95.187403
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Coupled Optical Phonons in the Ultrafast Dynamics of the Electronic Energy and Current Relaxation in Graphite

Abstract: Ultrafast charge carrier dynamics in graphite has been investigated by time-resolved terahertz spectroscopy. Analysis of the transient dielectric function and model calculations show that more than 90% of the initially deposited excitation energy is transferred to a few strongly coupled lattice vibrations within 500 fs. These hot optical phonons also substantially contribute to the striking increase of the Drude relaxation rate observed during the first picosecond after photoexcitation. The subsequent cooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

36
341
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(379 citation statements)
references
References 31 publications
36
341
0
2
Order By: Relevance
“…This amount of absorbed energy, however, would imply substantially higher temperatures than observed for either samples due to the small electronic specific heat of graphene (see the Supporting Information). A similar discrepancy between applied pump fluence and actual observed electronic temperature has been reported in a THz spectroscopy study on graphite 35 and is also observed in another recent TR-ARPES study. 21 Several reasons can be envisaged to account for the observed lower values.…”
Section: (C) This Is In Agreement With Our Previous Study On P-dopedsupporting
confidence: 86%
“…This amount of absorbed energy, however, would imply substantially higher temperatures than observed for either samples due to the small electronic specific heat of graphene (see the Supporting Information). A similar discrepancy between applied pump fluence and actual observed electronic temperature has been reported in a THz spectroscopy study on graphite 35 and is also observed in another recent TR-ARPES study. 21 Several reasons can be envisaged to account for the observed lower values.…”
Section: (C) This Is In Agreement With Our Previous Study On P-dopedsupporting
confidence: 86%
“…Because of electron-electron scattering the initial fs carrier excitation acquires a broadening in the energy distribution [10,20], and this distribution relaxes by electron-phonon coupling, leading to SCOP in the case of graphite. The time scale has been estimated to be on the order of 500 fs, for the electronphonon-coupling process, and 5 to 7 ps for the decay of SCOP into other modes [20,21]. These two characteristic time constants were obtained from time-resolved photoemission and THz spectroscopy experiments [20,21].…”
mentioning
confidence: 99%
“…With impulsive laser excitation the electronic bands are populated anisotropically, and, because energy and momentum have to be conserved, these carriers can excite only large momentum phonons. Such selective coupling leads to an efficient excitation of a subset of vibrations [20,21], socalled strongly-coupled-optical-phonons (SCOP), which ultimately decay to yield other vibrations. Because of electron-electron scattering the initial fs carrier excitation acquires a broadening in the energy distribution [10,20], and this distribution relaxes by electron-phonon coupling, leading to SCOP in the case of graphite.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In time-resolved experiments 23 two relaxation time scales are typically seen. A faster one, ∼ 100f s, usually associated with carrier-carrier intraband collisions and phonon emission, and a slower one, on a ps scale, corresponding to electron interband relaxation and cooling of hot phonons 24,25 .…”
Section: Saturable Absorptionmentioning
confidence: 99%